IN VITRO DIGESTIBILITY OF CARBOHYDRATE AND TOTAL GAS PRODUCTION OF GOAT MILK REPLACER BASED ON SURIMI WASTE POWDER AND KETCHUP DREGS POWDER - Afduha Nurus Syamsi; Lastriana Waldi; Tri Puji Rahayu (Universitas Tidar, 2018)
This research was aimed to evaluate the use of surimi waste powder and ketchup dregs powder as main material of milk replacer for dairy goat based on carbohydrate digestibility and total gas production. The research was held experimentally using in vitro method. Material used in the research was rumen fuilds taken from abbatoir Sokaraja, immediatelly after slaughter. Experimental design used completely randomized design (CRD) for carbohydrate digestibility with 4 treatments and replicate 5 times each. The results showed that the milk replacer has a significant effect on carbohydrate digestibility and total gas production (P <0.01). The research concludes that milk-based replacer of surimi waste powder and ketchup dregs powder has not been able to replace pure goat milk, because its carbohydrate digestibility is low and total gas production is unstable at the beginning and end of observation.Key words : dairy goat, milk replacer, surimi waste powder, ketchupdregs powder